Improving Students Reading Skill Through Short Story at Eleventh Grade of SMA Negeri 4 Kepulauan Aru: Reading Skill, Short Story, Getting Information - Louloulia, Yesika fieka; Rombepajung, Paula A.; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research is to describe using short story to improve students’ reading skill to getting information in reading. The subject of this research consisted of 17 students took one class at eleventh grade of SMA Negeri 4 Kepulauan Aru. The researcher used quantitative research method. In this quantitative research the design experimental the researcher used a pre-test and post-test design in one group, the data were collected using objective test in multiple choise format. The result of this research the students got significant improvement after the researcher teaching short story in the learning English for students. The result of the prestest students got lowest scores was 35,88 but after the researcher was gave treatment through short story for students the result of posttest the students got highes scores was 74,11. It means that, short story was successful in the teaching and learning English for students.